136 Small Diameter Penile Implants: A Survey on Current Utilization and Review of Literature. Issue 1 (1st April 2022) - Campbell, S; Kim, C; Allkanjari, A; Nose, B; Selph, JP; Lentz, A
ABSTRACT: Introduction: The small diameter penile implant (SDPI) is a modified IPP with a smaller diameter cylinder utilized in cases of anatomically small corpora or severe corporal fibrosis. SDPIs allow for patients to obtain useable erections, sometimes with the intent to upsize in the future. There is a dearth of literature on the optimal clinical scenarios for utilization of SDPIs, volume of SDPIs placed nationwide, and patient satisfaction results. Objective: Our aim is to identify current usage patterns and perceived patient satisfaction of SDPIs among urologic prosthetic surgeons. Methods: A 23-question online survey was distributed via email to physician members of the Sexual Medicine Society of North America (SMSNA) and Society of Urologic Prosthesis Surgeons (SUPS). The survey included questions regarding surgeon experience and volume, frequency of SDPI utilization, indications for SDPI, surgical strategy in the setting of SDPI (approach, use of concordant modeling/grafting), reservoir and pump management, and perceived infection risk and patient satisfaction. Results: 50 individuals responded to the survey, 48 of whom routinely utilized SDPIs. The most common indication for SDPI placement was corporal fibrosis from prior infection, followed by anatomically small corpora and priapism. The most common maximal dilation diameter was 10 mm (47%), with an additional 23% of respondents utilizing SDPI with 11 mm dilation. 75.4% of respondents sometimes or always intended to upsize to standard diameter cylinders in the future. 68.8% of surgeons routinely counseled patients on the possibility of reduced girth and rigidity with SDPI. Patient satisfaction was perceived to be comparable to standard diameter cylinders in 56.3% of respondents, while the remaining 43.6% believed it to be lower than traditional cylinders. Conclusions: SDPI are utilized by prosthetic surgeons in a variety of clinical situations and are frequently effective. Future research is needed to better characterize patient satisfaction and define which patients are best suited for SDPI. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Coloplast and Boston Scientific